Latin America Treads a Narrow Path to Growth : LAC Semiannual Report, April 2015 - de la Torre, Augusto (Washington, DC: World Bank, 2015)
The April 2015 LAC Semiannual Report covers the short-term prospects and provides an analysis of the external factors affecting the region's economic performance. The first chapter expands on LAC's economic outlook paying special attention to the global context and its effect on LAC’s economic performance. In this first Chapter we argue that the region experienced an external shock that has shaped growth in recent years, and that this shock is likely here to stay.